African traditional art forms, democratic governance and economic growth in Zimbabwe - Matiza, Vimbai M. (Unisa Press, 2022)
The article seeks to explore the role of African oral traditional art forms and governance in Zimbabwe for economic development. African philosophies, embedded in oral literature were part and parcel of the people’s life. Everybody participated in the activities that affected them in society. Thus African peoples used oral literature, which is dependent on the performer who formulates it on a specific occasion—this forms part of issues of governance. Some problems, which people, and Zimbabweans in particular are facing, emanate from colonialism, and have led them to believe that they had no culture or anything to shape their way of thinking. These problems have always been there, and people had a way of circumventing them through the philosophies that were embedded in their oral art forms. It is against this backdrop that the researcher seeks to explore the place of oral art forms; which include proverbs, riddles, folktales among others; and governance as vehicles to drive economic growth in Zimbabwe. The article is based on a conceptual method of study, where examples of oral art forms used have been taken from various speech communities in Africa. The researcher’s arguments are guided by the Afrocentric approach and the discussion establishes that issues of democracy and governance were part and parcel of indigenous people’s way of doing things, in a bid to achieve economic growth in their societies.